Geographic variations in the composition of myotoxins from Bothrops neuwiedi snake venoms: biochemical characterization and biological activity - Rodrigues, V. M.; Soares, A. M.; Mancin, A. C.; Fontes, MRM; Homsi-Brandeburgo, M. I.; Giglio, JR (Elsevier B.V., 1998)
(1) Venom pools from Bothrops neuwiedi (Bn) and from two subspecies, namely Bothrops neuwiedi pauloensis (Bnp) and Bothrops neuwiedi urutu (Bnu), collected in the States of São Paulo (SP) and Minas Gerais (MG), Brazil, were electrophoretically examined. Basic toxins with different isoelectric points were identified in the venom collected in São Paulo (BnSP). These toxins were absent in the corresponding pools from Minas Gerais (BnMG, BnpMG and BnuMG). (2) BnSP, but not BnMG, BnpMG or BnuMG, showed two myotoxins (pI congruent to 8.6 and 8.8, respectively) which were isolated by ion-exchange chromatography on CM-Sepharose. (3) From BnMG, three myotoxic isoforms (pI congruent to 8.2 and M-r = 13600) were isolated by chromatography on CM-Sepharose followed by reversed-phase high-performance liquid chromatography. (4) the chemical and biological characterization of these toxins showed a high similarity with the Lys-49 myotoxins from other bothropic venoms. (5) Doses up to 5 LD50 (i.p.) of p-bromophenacyl bromide alkylated BnSP-7 caused a total loss of lethality in 18-22-g mice, thus indicating that the LD50 was increased by greater than 5-fold. At this dose myotoxicity was also not detectable, but the edematogenic activity on the rat paw apparently did not change. (C) 1998 Elsevier B.V. All rights reserved.
Keywords: Bothrops neuwiedi; snake venoms; geographic variations; myotoxins; isomorphism; homology